ANALISIS KEMAMPUAN KOMUNIKASI MATEATIS SISWA PADA MATERI STATISTIKA DI KELAS VIII MTs S - Nunik Ardiana; Sinar Depi Harahap; Akmaluddin Pulungan (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to describe students’ mathematical communication ability on the topic statistics at the eighth grade students MTs S Aek Bonban. This research was conducted by using qualitative descriptive with the informants 1 mathematics teacher and 5 students ( 1 students who has high ability , 2 students who have average, and 2 students who have low ability) as the subject of the research. Interview and test were used in collecting the data. Students who has high ability able to understand and overcome the mathematical problem well based on the indicators, students who have medium ability able to understand the mathematical problem well but they are not able to overcome the mathematical problem well based on the indicators (they able overcome 2 indicators), and students who have low ability are not able to understand the mathematical problem well and they also are not able to overcome the mathematics problem well ( they able to overcome 1 indicators).